Bilingual education in the Philippine context - Nelly l. Cubar (Journal of Modern Languages, 2017)
This paper consists of five parts: 1) a preliminary describing the background of bilingual education in the Philippines, 2) the paradox of bilingual education in the Philippines, 3) the complementarity or Filipino and English 4) the nature or English borrowings in Filipino and 5) some final remarks focusing on the intellectualization or Filipino through English.